Symposium 4: Studying Informal Technology-Mediated Learning Networks: A Case Study on eTwinning Analytics: Keynote Abstract - Vuorikari, Riina (Proceedings of the International Conference on Networked Learning, 2012)
The symposium has, furthermore, a keynote by Riina Vuorikari: “Studying Informal Technology-Mediated Learning Networks: A Case Study on eTwinning Analytics”. The keynote outlines the context for the Tellnet research and its chosen methods to study professional social networks (e.g. social network analysis, information visualisation, future forecasting), and illustrates the value of analysing users’ interactions with various tools and interfaces to provide insights into professional networks regarding cooperation and collaboration.